Influence of Different Pigment Incorporation Methods on Color, Dimensional Stability, and Detail Reproduction of Silicones - Nobrega, Adhara Smith [UNESP]; Malavazi, Estefania Marrega [UNESP]; Melo Neto, Clóvis Lamartine De Moraes [UNESP]; Ervolino, Isabela Caroline De Sousa [UNESP]; Bannwart, Lisiane Cristina [UNESP]; Bertoz, André Pinheiro De Magalhães [UNESP]; Goiato, Marcelo Coelho [UNESP] (Thieme, 2019)
Objective: To analyze the influence of three pigment incorporation methods on color change, dimensional stability, and detail reproduction of the MDX4-4210 and A-2186 silicones. Materials and Methods: The A-2186 and MDX4-4210 silicones were used for preparation of samples, with the incorporation of bronze, black and pink pigments, usingconventional, mechanical, and industrial incorporation methods. Samples were submitted to the initial readings of color (n = 10; 22-mm diameter × 2-mm thickness), detail reproduction, and dimensional stability (n = 10; 30-mm diameter × 3-mm thickness). Readings were also taken at the end of 252, 504 and 1,008 hours of aging cycles. Results: Quantitative data were evaluated by ANOVA and Tukey test, with a level of significance of 5%. The mechanical and industrial methods caused smaller color changes of all samples compared with the conventional method (p < 0.05). In most cases, the mechanical and industrial methods caused less samples' contraction than the conventional method after aging (p < 0.05). The color change values increased progressively in each aging period for all samples (p < 0.05). The contraction values increased progressively in each aging period for all samples (p < 0.05). In the qualitative analysis of detail reproduction, all samples presented full reproduction of the three grooves, with accurate angles, initially and after the aging periods. Conclusions: The industrial and mechanical methods showed the best results for color and dimensional stability. Despite the statistical differences, all pigment incorporation methods generated acceptable dimensional and color changes of the MDX4-4210 and A-2186 silicones, regardless of the pigment and aging. In addition, the detail reproduction was satisfactory after aging periods in all cases of this study, showing the excellent quality of the A-2186 and MDX4-4210 silicones.
Keywords: maxillofacial prosthesis; oncology; physical properties; silicone elastomers